The Efficiency of Commercial Banks in Financing MSME in Indonesia - Puspitasari, Saras Meilia; Rusdarti, Rusdarti; Murwatiningsih, Murwatiningsih (Journal of Economic Education, 2019)
This study aims to analyze the efficiency of commercial banks in MSME financing before and after the existence of Bank Indonesia Regulation Number 17/12/PBI/2015 in Indonesia. The data used in this study was data originating from 52 commercial banks that were recorded in the Financial Services Authority (OJK). The data analysis technique used in this study is a non-parametric method with a Data Envelopment Analysis (DEA) approach with input variables consisting of financial capital, third-party funds, operational costs, and the output variable used is MSME financing. The results showed that before the existence of Bank Indonesia Regulation Number 17/12/PBI/2015 there were seven commercial banks that were efficient in financing MSMEs, and after that regulation, there were twelve efficient commercial banks in financing MSMEs. The results showed that the significance value of 0.955 was greater when compared with the alpha value of 0.05. This proves that there is no difference in efficiency before and after the existence of Bank Indonesia Regulation Number 17/12/PBI/2015.